Development of structure and properties during thermal calendering of polylactic acid (PLA) fiber webs (eXPRESS Polymer Letters)
Due to its thermoplastic and biodegradable nature, poly(lactic acid) (PLA) holds good promise in its increasing use in the form of fibers for medical, agricultural, apparel, upholstery, hygiene, and other applications. Most of the research being done on PLA fibers is to understand their production by melt spinning, solution spinning, and the structure-property relationships during fiber formation. Nonwovens are one of the important forms of the materials into which PLA polymer can be converted to create many useful products. Thermal bonding is the most widely used bonding technique employed to impart strength, and other useful characteristics to the nonwovens. However, there is limited research done to study the behavior of PLA fibers during thermal bonding of nonwovens. Hence the research was carried out to investigate the thermal bonding of nonwovens made from PLA staple fibers. The PLA fibers were carded and then calendered at different temperatures. The webs were characterized for their structure and properties. The observed results are discussed with respect to the investigated processing conditions.